Paul, the Law, and the Jewish people - Sanders, Ed Parish, 1937- (London, Uk SCM, 1983)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Epistles of Paul -- theology; Paul, the apostle, saint; Sociology, biblical